Czy Synod biskupów to zagrożenie demokratyzacji Kościoła? Kilka uwag na kanwie medialnej krytyki Synodu - Młynarczyk, ks. Adam (Łódzkie Studia Teologiczne, 2025)
The overview of the Synod on Synodality presented in the media, especially on the Internet, is not unambiguous. Among the critical voices, there is a claim that the Synod might be a part of a process of democratization the Catholic Church. This paper, which is based on a lecture delivered at a national scientific conference “Synodality – An Opportunity or a Threat for the Church”, is an attempt to respond to the question of whether the Synod of Bishops, as an institution, might actually pose a risk of democratizing the Church, or, on the contrary, is an instrument that assists the Bishop of Rome in his pastoral mission, in fruitful communion with bishops from all over the world.